MODEL OF PRODUCTION FUNCTION AND PRODUCTION RISK OF CATFISH (Clarias sp) FARMING IN KEDIRI DISTRICT - Mariyana Sari; Edi Susilo; Supriyadi Supriyadi; Kartika Intan Abdillah; Chusnia Asshovani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
One of the risks which is faced by catfish farmers frequently is production risk. The existence of production risk encourages farmers to make decisions to allocate production inputs. The behavior of farmers in facing production risk will be the basis for making decisions related allocation of production inputs to be used in catfish farming. This study aimed to analyze the effect of the use of production factors on production and production risk of catfish farming in Kediri District. Data in this study used primary data which is obtained from observations and structured interviews. The type of cross section data is gained from 40 catfish farmers. Descriptive and inferential statistical analysis method is used to analyse the data in this study. Analysis of production function data and production risk with the Just and Pope model approach. This study depicts that feed use and years of farming experience have a significant influence on catfish farming production. Increasing farming experience has a significant effect in terms of reducing production risk of catfish farming. Catfish farmers should use good quality of catfish seeds, improve their skills in cultivation techniques continuously, and communicate horizontally with fellow catfish farmers in order to be perceptive in exchanging experiences. Farmers must increase their experience to mitigate production risks.